Evaluation of expression analysis of putrescine n-methyltransferase gene during different stages of growth in the medicinal plant Physalis divaricata (Solanaceae) - ELHAM MOALLEM; ABDOLLAH GHASEMIPIRBALOUTI; TAHER NEJADSATTARI; ALIREZA IRANBAKHSH; IRAJ MEHREGAN (Society for Indonesian Biodiversity, 2017)
Moallem E, Ghasemipirbalouti A, Nejadsattari T, Iranbakhsh A, Mehregan I. 2017. Evaluation of expression analysis of putrescine n-methyltransferase gene during different stages of growth in the medicinal plant Physalis divaricata (Solanaceae). Biodiversitas 18: 1430-1437. Physalis divaricata (Solanaceae) is one of the most prevalent weeds in summer crops. Putrescine Nmethyltransferase (PMT) is a key enzyme in the biosynthesis of nicotine, tropane alkaloids atropine, scopolamine, cocaine, and calystegines. The present study set to compare PMT gene expression during different growth stages of Ph. divaricata using RT-qPCR assay. RNA extraction was performed from root and leaf samples of a total number of 40 individuals Ph. divaricata at different growth stages (late vegetative and fruiting stages) collected from southwestern Iran. RT-qPCR of cDNA reversely synthesized from RNA was carried out using SYBRÂ®Premix Ex TaqTM II kit. PMT gene expression levels were analyzed using Î”Î”CT method. The results showed that expression level of PMT in late vegetative stage samples was significantly higher compared to fruiting stage samples. The expression level of PMT similarly changed in root and leaf samples. Direct visualization of alkaloids in different tissues using Wagner histochemical tests showed more concentrations of alkaloids in leaf idioblasts and root stele.